Mapping the tilt of the Milky Way bulge velocity ellipsoids with ARGOS and Gaia DR2. Issue 2 (14th January 2021) - Simion, Iulia T; Shen, Juntai; Koposov, Sergey E; Ness, Melissa; Freeman, Kenneth; Bland-Hawthorn, Joss; Lewis, Geraint F
ABSTRACT: Until the recent advent of Gaia Data Release 2 (DR2) and deep multi-object spectroscopy, it has been difficult to obtain 6D phase space information for large numbers of stars beyond 4 kpc, in particular towards the Galactic Centre, where dust and crowding are significant. We combine line-of-sight velocities from the Abundances and Radial velocity Galactic Origins Survey (ARGOS) with proper motions from Gaia DR2 to obtain a sample of ∼7000 red clump stars with 3D velocities. We perform a large-scale stellar kinematics study of the Milky Way bulge to characterize the bulge velocity ellipsoids in 20 fields. The tilt of the major-axis of the velocity ellipsoid in the radial-longitudinal velocity plane, or vertex deviation, is characteristic of non-axisymmetric systems and a significant tilt is a robust indicator of non-axisymmetry or bar presence. We compare the observations to the predicted kinematics of an N -body boxy-bulge model formed from dynamical instabilities. In the model, the lv values are strongly correlated with the angle (α) between the bulge major-axis and the Sun-Galactic centre line of sight. We use a maximum likelihood method to obtain an independent measurement of α, from bulge stellar kinematics alone, performing a robust error analysis. The most likely value of α given our model is α = (29 ± 3) ○, with an additional systematic uncertainty due to comparison with one specific model. In Baade's window, the metal-rich stars display a larger vertex deviation ( lv = −40 ○ ) than the metal-poor stars ( lv = 10 ○ ) but we do not detect significant lv −metallicity trends in the other fields.